Prediction of upgrade to clinically significant prostate cancer in patients under active surveillance: Performance of a fully automated AI‐algorithm for lesion detection and classification - Oerther, Benedict; Engel, Hannes; Nedelcu, Andrea; Schlett, Christopher L.; Grimm, Robert; Busch, Heinrich; Sigle, August; Gratzke, Christian; Bamberg, Fabian; Benndorf, Matthias (The Prostate, 2023)
Background Multiparametric MRI (mpMRI) improves the detection of aggressive prostate cancer (PCa) subtypes. As cases of active surveillance (AS) increase and tumor progression triggers definitive treatment, we evaluated whether an AI‐driven algorithm can detect clinically significant PCa (csPCa) in patients under AS. Methods Consecutive patients under AS who received mpMRI (PI‐RADSv2.1 protocol) and subsequent MR‐guided ultrasound fusion (targeted and extensive systematic) biopsy between 2017 and 2020 were retrospectively analyzed. Diagnostic performance of an automated clinically certified AI‐driven algorithm was evaluated on both lesion and patient level regarding the detection of csPCa. Results Analysis of 56 patients resulted in 93 target lesions. Patient level sensitivity and specificity of the AI algorithm was 92.5%/31% for the detection of ISUP ≥ 1 and 96.4%/25% for the detection of ISUP ≥ 2, respectively. The only case of csPCa missed by the AI harbored only 1/47 Gleason 7a core (systematic biopsy; previous and subsequent biopsies rendered non‐csPCa). Conclusions AI‐augmented lesion detection and PI‐RADS scoring is a robust tool to detect progression to csPCa in patients under AS. Integration in the clinical workflow can serve as reassurance for the reader and streamline reporting, hence improve efficiency and diagnostic confidence.